Analysis of the scientific production about radio indexed in the Web of Science in the category of Film, Radio & Televisión: 2000-2016 - Luz Mª Romo-Fernández (Cuadernos de Documentación Multimedia, 2018)
This work provides an overview of the research on scientific production on radio during the period 2000-2016. For the analysis, the production contained in the magazines belonging to the category of Film, Radio, Television in the Web of Science was used. A total of 318 publications are extracted and data have been calculated such as number of documents per year, countries of affiliation of the authors, thematic categories related to the category selected as object of study, the sources in which the works are disseminated, the language of publication, documentary typology and average number of citations per document. The results of the study show that there is a stable trend throughout the period, publishing articles where about 45% of the authors are affiliated with a US institution and in most disciplines more than 60% of the publications are in English.